Multicystic nephroma: a rare benign renal tumor with diagnostic predicament - Venkatesh, Kusuma; Ravindra, Savithri; Agarwal, Ankita; Malhotra, Ankit (International Journal of Research in Medical Sciences, 2018)
Multi cystic Nephroma is a rare benign tumor of kidney occurring in adults which has clinical, radiological and morphological features causing diagnostic dilemma as it mimicks other cystic renal lesions. Distinguishing it from a cystic renal carcinoma is very important. Multicystic nephroma is usually unilateral, more common in females, presenting as a well capsulated mass lesion with multiple non communicating cysts lined by hobnailing epithelium. A similar lesion occurring in children represents a well differentiated nephroblastoma. The case presented here was a female patient complaining of pain in the left flank and had a mass lesion which was diagnosed as cystic renal cell carcinoma radiologically. The nephrectomy specimen showed a multilocular cystic mass well delineated from adjacent renal parenchyma. Histopathologically the cysts were lined by hobnail type of epithelium and separated by fibrocollagenous stroma. The stroma had hyalinised areas, chronic inflammatory cell infiltration and foci of mature adipose tissue. No atypia or mitoses were seen in the epithelium or stromal cells. Based on the histological criteria a diagnosis of multicystic nephroma was made. It is important to make a diagnosis of multicystic nephroma based on histomorpholgical criteria as it relieves the patient from the burden of a malignant lesion.